COMPARISON OF CARBON, NITROGEN AND WATER BUDGETS ON VENUS AND THE EARTH - Lécuyer C.; Simon L.; Guyot F. (My University, 2000)
Carbon, nitrogen and water abundances at the surfaces of Earth and Venus are compared in order to investigate the distributions of these elements between fluid and solid envelopes in both planets. The atmosphere of Venus contains about twice more carbon (1.25×1020 kg of C) and nitrogen (4.8×1018 kg of N) than the atmosphere, hydrosphere and sediments of the Earth (5.4×1019 kg of C and 3×1018 kg of N). After scaling to the planetary masses, surface excesses of 1×1020 kg of C and 2.7×1018 kg of N are calculated for Venus relatively to the Earth. The simplest proposed explanation is the storage of 25 ppm of C and 0.7 ppm of N in the Earth mantle due to lithospheric subduction, a mechanism not operating on Venus. Following the same line of arguments, the Earth has an excess surface water of about 1.2×1021 kg of H2O, when compared to Venus. Under the hypothesis of a primordial sizable water mass on Venus, thermodynamic modeling of mineral stabilities reveals that hydrous minerals are stable at the P–T conditions of both the surface and the deep crust of Venus, and thus could be the carriers of the missing Venusian water. A combination of crustal hydration and hydrogen escape processes may explain the present-day low amount and high deuterium/hydrogen (D/H) ratio (2.5×10−2) of water in the Venusian atmosphere relatively to the Earth’s hydrosphere (1.55×10−4). Alternatively, if the high D/H ratio of Venus only resulted from hydrogen escape, the reservoir of remaining oxygen must have been involved in the oxidation of a rock layer of about 50 km in depth.